A comparison of the effects of carbon dioxide and hydrogen ions on the function of the isolated rat heart. - Belair, Ernest J. (University of Ottawa (Canada), 1965)
Isolated rat hearts were perfused by a modified Langendorff method to compare the effects of CO2 and H+ on their function. Carbon dioxide had a rapid negative inotropic effect which was not dependent on the perfusate pH, or on the concurrent negative chronotropic effect and change in coronary resistance. Carbon dioxide caused a negative chronotropic effect which was due, in part, to the decreased perfusate pH. This negative chronotropic effect was not due to the concurrent negative inotropic effect or to the changes in coronary resistance. Intermediate concentrations of CO2, between 6% and 20%, were found to have intermediate negative inotropic and chronotropic effects. Carbon dioxide at concentrations of 18% and 20% caused coronary resistance to increase. This increase was independent of perfusate pH, rate or tension changes. Carbon dioxide concentrations between 6% and 16% caused coronary resistance to decrease. Decreasing oxygen from 95% to 80% caused a positive inotropic effect. Perfusates saturated with 20% CO2 caused the release of some basic substances from the heart. This release was not dependent on decreased perfusate pH.
Keywords: Biology, Animal Physiology.